ECONOMETRICAL METHODS OF MODELING AND FORECASTING THE ECONOMY OF THE REGION (FOR EXAMPLE, THE ROSTOV REGION OF RUSSIA) - Runova, Л.П. (Journal of Information Technologies in Education (ITE), 2012)
This article attempts to construct a model predicting the region's economy using econometric methods. Research is being conducted by the example of the Rostov region of Russia.